Customized Management of Hypothyroidism Through Ayurvedic Intervention (AYUSHDHARA, 2024)
Hypothyroidism is a condition characterized by decreased thyroid hormone production, resulting in diminished metabolic rate, manifesting as a spectrum of symptoms from subclinical hypothyroidism (SCH) to overt hypothyroidism, with associated physiological derangements. In this study Anu taila Nasya was used. A female patient age 22 years weight 58kg was diagnosed with Hypothyroidism from a clinical point of view. There was a dyspnoea, loss of appetite, weakness, weight gain in the last 2 months with irregular menstruation in the past 4 months. Blood report of TSH value shows 6.35µIU/ml. She was treated with Panchakarma Anu taila Nasya followed by Shamana Chikitsa for 6 months follow up. The result of patient was assessed on the basis of subjective and objective criteria. The TSH value after the treatment shows significant result of 4.65µIU/ml. Significant changes were also observed in the clinical features before and after the treatment. So, this study concludes, Anu taila Nasya has Ushna Tikshna dravyas and Vata Kaphahara properties which causes Shodhana and Lekhana of Kapha doshas, along with palliative treatment has shown good and significant result by its Guna-dharma and Shodhana action in hypothyroidism. Hence it can be used as a preferred treatment for hypothyroidism.